Die Identifikation kryptojüdischer Frauen auf der iberischen Halbinsel und in deren Kolonien mit biblischen Frauengestalten (lectio difficilior, 2009)
The term crypto-Judaism is used to describe the secret maintenance of Jewish practices by people of Jewish origin who have converted publicly to another faith. In the Iberian Peninsula and its colonies this phenomenon resulted from the forced and mass conversions in the 14th and 15th centuries on Iberian soil. Over the past two decades a significant number of studies has demonstrated the central role of women in the preservation and continuation of crypto-Judaism. The absence of traditional Jewish institutions led by men and the unusual importance of the home for the judaizing people clearly contributed to the crucial role of women in the perpetuation of Judaism. Many of them preserved Jewish practices and transmitted Jewish traditions to their children. This shows a great commitment to their religious heritage and a self-perception as a part of the people of Israel. The article corroborates this idea from a new perspective: The identification of some judaizing women with biblical heroines such like Esther and Judith should be taken into account, as they find in these biblical women female role models for their lives and their worldview and they considerate them as reference figures, trough whom they can affirm their activism and their own role in crypto-Judaism. The mention of Jacob’s granddaughter in a Mary Gómez’ prophecy is remarkable; despite being a particular case it can reveal a lot about the thinking of some crypto-Jewish women.